The misallocation in the Chinese land market - Xuan Fei (Bank of Finland, Institute for Economies in Transition (BOFIT), 2020)
This paper proposes a spatial equilibrium model to quantify welfare losses from land market distortions in China. In the model, heterogeneous firms in a variety of sectors choose their locations across regions with costly trade, frictional labor migration, and land market distortions. We match land transaction and firm-level survey data to estimate land market distortions for firms. Misallocation arises when similar firms are faced with land prices that effectively prevent productive firms from establishing in large cities where they can benefit from agglomeration forces and access to higher productivity. Our framework incorporating land market distortions also helps clarify the mystery of China's undersized cities, a phenomenon noted by Au and Henderson (2006) and Chauvin et al. (2017). Our estimates suggest large negative effects of land policies on the economic welfare in China. We end with a counterfactual exercise that suggests that a coordinated land and labor migration reform would generate welfare gains and reduce regional inequality
URN:NBN:fi:bof-202010212445
Keywords: F16; L22; L51; O47; R14; R30; 330; Misallocation; agglomeration; firm behaviors; land; productivity; city; China